DEVELOPMENT OF BUDDHIST SONG AND MOVES AS LEARNING MEDIA FOR CHARACTER EDUCATION BASED ON 2013 CURRICULUM: PENGEMBANGAN GERAK DAN LAGU BUDDHIS SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN KARAKTER BERBASIS KURIKULUM 2013 - Widayanti, Wiwik; Setyaningsih, Setyaningsih; Endah Ekowati, Wilis Rengganiasih (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2019)
This study aims to determine the process of making Buddhist song and moves as character education learning media based on the 2013 Curriculum for students of Kenteng 1 Elementary School Susukan Sub district, Semarang Regency. This type of research is Research and Development (RnD) level 4. The techniques for collecting data used observation, questionnaires, interviews, and documentation. The credibility of the data used is qualitative and quantitative methods. The data analysis technique used a combination of Exploratory Sequential Mixed Methods. Based on the research and discussion that had been carried out, the process of making moves and song based on 2013 Curriculum consisted of several stages as follows: (a) analyze, the teacher needed student-centered learning media and which contains character values. This need was followed up so as to produce two Buddhist song and moves products. (b) design, the steps taken include the creation of musical instruments and song lyrics; development of moves; recorded music, vocals, and moves. (c) develop, products that were developed contained character values ​​such as obedience to worship, tolerance, caring, confidence, responsibility, discipline, and concentration. (d) implement, the product was tested on the first and second grade students, as many as nine students. (e) evaluate, improvements that needed to be considered were musical arrangements and expressions of the performer and song. The end result is the Buddhist song and moves with the title